Rapid multiplication of cassava: IITA research guide, No. 51 - Otoo, J. (1994)
Cassava has a low multiplication ratio compared with other crops, especially seed-propagated crops. Rapid multiplication techniques are available to increase the multiplication ratio. Three types of ministem cuttings can be produced from a cassava stem. After sprouting in nursery beds, or polythene bags without soil, the ministems can be planted into the field to produce normal cassava plants from which cassava cuttings can be prepared for distribution to farmers.